Determination of technological parameters of Artemisia Gmelinii herb - Сакипова, Зуриядда Бехтемировна; Маматова, Алия Серикжанова; Кисличенко, Виктория Сергеевна; Новосел, Елена Николаевна (ScienceRise: Pharmaceutical Science, 2016)
The continuous research of the most frequently used raw material, perspective for development of new remedies on its basis, is forehanded objective of pharmacy. The article is devoted to determination of technological parameters of Artemisia Gmelinii herb, the endemic of the Republic of Kazakhstan. It was found, that the given species of Artemisia is a rich source of medicinal compounds, and has a wide spectrum of therapeutic activity. Nevertheless, in most cases Artemisia is used only in traditional medicine. Aim. The aim of research was determination of technological and some pharmacopoeial parameters of Artemisia Gmelinii for the further development of technology of phytotherapeutic drugs in different dosage forms, and mass balance calculation. Methods. Both pharmacopoeial and non-pharmacopoeial methods were used. Results. The aerial part of Artemisia Gmelinii Web. et Stechm. of Kazakhstan populations was studied. To develop the optimal methods of extraction, prediction and rationing quality of extract, technological properties of the given raw material – herb of Artemisia Gmelinii – were determined: bulk density – 0,23 g/сm3; fineness – 3–5 mm; specific weight – 1,40 g/сm3; bulk mass – 0,50 g/сm3; porosity – 0,59 g/сm3; fenestration – 0,54 g/сm3; free bed volume – 0,81 g/сm3; extracting agent absorption coefficient: aqua – 4,4 ml/g; ethanol 40 % – 3,9 ml/g; ethanol 70 % – 3,1 ml/g. Technological specifications and some pharmacopoeial parameters of the finished product quality were developed on the basis of the obtained data. Conclusion. As a results of research, technological properties of Artemisia were determined: bulk density, fineness, specific weight, bulk mass, porosity, fenestration, free bed volume, and extracting agent absorption coefficient